Orbital and rotational atherectomy during percutaneous coronary intervention for coronary artery calcification. Issue 1 (17th October 2017) - Lee, Michael S.; Gordin, Jonathan S.; Stone, Gregg W.; Sharma, Samin K.; Saito, Shigeru; Mahmud, Ehtisham; Chambers, Jeff; Généreux, Philippe; Shlofmitz, Richard
Abstract: Severe coronary artery calcification (CAC) increases the complexity of percutaneous coronary intervention (PCI) by inhibiting optimal stent expansion, leading to an increased risk of death, myocardial infarction, repeat revascularization, and stent thrombosis. Coronary atherectomy modifies and debulks calcified plaque to facilitate PCI. Although there is no clear consensus, and further studies are needed, the decision to perform atherectomy should be based upon the presence of fluoroscopic CAC or with the use of intravascular imaging. The management of CAC in the modern era relies on rotational and orbital atherectomy to prepare the lesion to facilitate stent delivery and optimal expansion. While the two technologies differ in equipment, technique, and mechanism of action, the available literature suggests similar efficacy and safety of the two systems, although head‐to‐head comparisons are limited. While rotational and orbital atherectomy have been shown to have excellent procedural success in terms of facilitating stent delivery, no system has been shown to reduce long‐term major adverse cardiovascular events, although the definitive trial for orbital atherectomy has not been completed. Additional trials are needed to find the population who would derive the most benefit of atherectomy and to compare the two systems in a prospective manner.